Air Navigation: The Method of Airborne Vehicles' Classification Based on Fuzzy Colored Petri Nets - Linnik, Ivan; Linnik, Elena; Timirgaleeva, Rena; Grishin, Igor; Tamargazin, Aleksander (2021 29th Conference of Open Innovations Association (FRUCT), 2021)
Based on mathematical methods of fuzzy colored Petri nets proposed is a method of airborne vehicles' identification in controlled airspace allowing to reduce the dependence of the degree of fuzzy net model of the corresponding software's verification on the degree of dynamic interacting processes in the subject area. Proposed are the data of fuzzy rule-oriented requirements of the fuzzy logical system of airborne vehicles' classification in the process of airspace control. Developed is a unified algorithm of these requirements' implementation. Further, the fuzzy rule-oriented requirements are in structural conformity with the requirements of the Sugeno fuzzy logical system of the first-order. This view of the airborne vehicles' classification process using the fuzzy logical system allows considering both the non-stochastic and subjective nature of operators' decision-making. The developed unified algorithm of the fuzzy rule-oriented requirements' implementation within the Sugeno system of the first-order is the basis for the software of the fuzzy logical system of airborne vehicles' classification.